ENT 600 : New product development : Magnify group sdn bhd / Mohd Sharmizam Ishak ...[et al.] - Ishak, Mohd Sharmizam; Ibrahim, Mohd Azhar; Zamri, Inna Farina; Mat Zin, Noor Hidayu (2019)
As the world's population continues to grow, so does the amount of garbage that people produce. On-the-go lifestyles require easily disposable products, such as soda cans or bottles of water, but the accumulation of these products has led to increasing amounts of plastic pollution around the world. As plastic is composed of major toxic pollutants, it has the potential to cause significant harm to the environment in the form of air, water, and land pollution. Put simply; plastic pollution is when plastic has gathered in an area and has begun to negatively impact the natural environment and create problems for plants, wildlife, and even the human population. Often this includes killing plant life and posing dangers to local animals. Plastic is an incredibly useful material, but it is also made from toxic compounds known to cause illness, and because it is meant for durability, it is not biodegradable. According to a report published by the Ellen MacArthur Foundation, if the current rate of plastic pollution continues, there will be more plastic in the oceans than there are fish by the year 2050. Right now, one garbage truck of plastic is dumped into the ocean every minute. Though at first this small straw may not seem like a lot, when its usage is added up, plastic straws create a big problem for the environment. Straws are an easy thing for everybody to get started on when approaching the enormous issue of plastic pollution. Thus, in order to eliminate the scourge of plastic straws, groups such as Lonely Whale, Last Plastic Straw, Straw Free, and Be Straw Free have sprung up. In addition, many other great alternatives for plastic straws have also been introduced, such as metal straws and rice straws. I would like to suggest for us Malaysians to try this innovation in our country in order to eliminate the scourge of plastic straws.